Growth, plant water relation and photosynthesis rate of young Theobroma cacao as influenced by water stress - Ismail, Mohd Razi; Hassan, Abdul Halim; Dola, Kamariah; Jalil, Mohd Noh (Universiti Pertanian Malaysia, 1992)
The effects of duration of water stress on the growth and physiological changes of young Theobroma cacao plants were investigated. Water was withheld for 4, 8, and 12 days before watering for a period of 20 weeks. Leaf area, leaf area index, leaf, root and stern dry weights were significantly reduced with duration of withholding water. There was a close relationship between photosynthesis rate and changes in leaf water potential. Leaf photosynthesis rate was reduced when leaf water potential dropped below -2.0 MPa. Determinations of plant processes showed a clear variation between three local clonal plants i.e. KKM 4, KKM 5 and KKM 25 with KKM25 recording the highest leaf water potential, stomatal conductance and leaf photosynthesis rate.